Traditional Feeding Practices with Brewer’s Cake (Xaj pitha) on Growth Performance of Crossbred Pigs - Kalita, A.; Saharia, J.; Deka, R. J.; Bora, J. R.; Haque, A.; Saikia, K.; Saikia, G.; Deka, S. D.; Talukdar, M. (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was conducted for a period of 6 months from April, 2022 to September, 2022 under the Department of Livestock Production and Management, at institutional pig farm (30- Sow Teaching Unit), College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati, Assam, India to evaluate the effect of feed prepared by using Xaj pitha on crossbred Hampshire pigs. The experiment was conducted to study the impact of feeding indigenously fermented feed on growth performance of crossbred Hampshire pigs under farm condition. A total of 18 weaned Crossbred Hampshire pigs irrespective of sex with an average age of around 8 weeks were randomly selected for the study. Thereafter, the piglets were divided into three experimental treatment groups viz., Standard Conventional feed (T0), Indigenously fermented feed by using traditional Brewer’s Cake (Xaj pitha) (T1) and boiled feed (T2). Findings revealed a significant effect (p<0.01) on final body weight of pigs fed with indigenously fermented feed when compared to boiled feed and conventional feed. No significant difference was found in average final daily body weight gain, feed consumption and feed conversion efficiency of the crossbred Hampshire pigs in different experimental groups. The digestibility co-efficient of crude protein and ether extract were significantly higher (p<0.01) in group fed with fermented feed as compared to groups given boiled feed and conventional feed. From the present study it can be concluded that pigs fed with fermented feed by using traditional brewer’s Cake (Xaj pitha) had better results in comparison to pigs given conventional feed and boiled feed.